Exogenously Applied Salicylic Acid Boosts Morpho-Physiological Traits, Yield, and Water Productivity of Lowland Rice under Normal and Deficit Irrigation - Heba Abdelhamid El Sherbiny; Essam F. El-Hashash; Moamen M. Abou El-Enin; Randa Samir Nofal; Taia A. Abd El-Mageed; Eman Mohamed Bleih; Mohamed T. El-Saadony; Khaled A. El-Tarabily; Ahmed Shaaban (Agronomy, 2022)
The main constraint on rice cultivation in the Mediterranean area is the limited irrigation and its large water consumption. In addition, rice is very sensitive to drought conditions because of drought stress on morpho-physiological traits and yield reduction. The application of salicylic acid (SA) has been noticed to be very effective in alleviating the adverse effects of drought stress on rice. The current investigation was conducted as a split-split arrangement under a randomized complete block design with two lowland rice cultivars (Giza177 and Giza179) and SA as a foliar application at four concentrations (0, 400, 700, and 1000 µM) under normal and drought conditions. The results showed that plant growth, leaf photosynthetic pigments, yields, and the most studied traits were significantly affected by irrigation (I), cultivar (C), and SA concentration (p ≤ 0.05 or 0.01). The interaction effect of I × C × SA was only significant on the carotenoids content (p ≤ 0.05). The reduction in grain yield and most studied traits was more pronounced under drought conditions. The Giza179 proved to be a drought-tolerant cultivar under all SA concentrations under drought conditions, while Giza177 was a drought-sensitive cultivar. The application of 700 µM SA gave the best grain yield in both rice cultivars under drought conditions compared to other SA concentrations. Grain yield for normal irrigation (Yp) and drought stress (Ys) conditions were highly positively correlated with indices of the mean productivity (MP), geometric mean productivity (GMP), stress tolerance index (STI), yield index (YI), yield stability index (YSI), drought resistance index (DI), harmonic mean (HM), and golden mean (GOL). While they are highly negatively correlated with the indices of the stress susceptibility index (SSI), tolerance index (TOL), yield reduction ratio (YR), stress susceptibility percentage index (SSPI), and abiotic tolerance index (ATI). It could be concluded that SA, as a growth regulator, could be used to alleviate the harmful effect of inadequate water availability in soil on rice cultivars as well as to improve the growth, water productivity, and grain yield.